2018
DOI: 10.1016/j.neuropharm.2017.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-gated sodium channel β subunits: The power outside the pore in brain development and disease

Abstract: Voltage gated sodium channels (VGSCs) were first identified in terms of their role in the upstroke of the action potential. The underlying proteins were later identified as saxitoxin and scorpion toxin receptors consisting of α and β subunits. We now know that VGSCs are heterotrimeric complexes consisting of a single pore forming α subunit joined by two β subunits; a noncovalently linked β1 or β3 and a covalently linked β2 or β4 subunit. VGSC α subunits contain all the machinery necessary for channel cell surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 166 publications
(372 reference statements)
1
59
0
1
Order By: Relevance
“…The same voltage-gated sodium channel gene set was previously implicated in schizophrenia in an analysis of compound heterozygous mutation [18], a model that cannot be adequately tested in the present dataset given the inability to phase very low frequency variation. In addition to previous genetic support in schizophrenia, we note sodium channels have high biological plausibility given that mutations in this gene set have been associated with other neurodevelopmental disorders, including some forms of epilepsy and developmental delay [2022]. In the current study, no single sodium channel gene was significantly associated with schizophrenia (after correction for multiple testing), with the most significant gene being SCN7A ( P uncorrected = 0.0012).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The same voltage-gated sodium channel gene set was previously implicated in schizophrenia in an analysis of compound heterozygous mutation [18], a model that cannot be adequately tested in the present dataset given the inability to phase very low frequency variation. In addition to previous genetic support in schizophrenia, we note sodium channels have high biological plausibility given that mutations in this gene set have been associated with other neurodevelopmental disorders, including some forms of epilepsy and developmental delay [2022]. In the current study, no single sodium channel gene was significantly associated with schizophrenia (after correction for multiple testing), with the most significant gene being SCN7A ( P uncorrected = 0.0012).…”
Section: Discussionsupporting
confidence: 56%
“…The sodium channel set contains 14 genes, 10 encoding alpha subunits involved in generating action potentials [21], and 4 beta subunits which, in association with alpha subunits, modulate their gating and cellular excitability [22]. In the present study, the evidence for association derives from mutations in alpha subunits, although the absence of signal in beta-subunits might simply reflect low power (there are fewer beta-subunits, of which paralog conservation scores are only available for SCN2B and SCN4B , whereas paralog conservation scores are available for all 10 alpha subunits).…”
Section: Discussionmentioning
confidence: 99%
“…These alterations may be consequences of the complex nature of subtle intramolecular interactions within the channel, as well as intermolecular interactions between the channel and a great variety of regulatory proteins. So far, Nav‐β subunits (Hull & Isom, ), calmodulin, fibroblast growth factor homologous factors (Wang et al . ; Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…as intermolecular interactions between the channel and a great variety of regulatory proteins. So far, Nav-β subunits (Hull & Isom, 2018), calmodulin, fibroblast growth factor homologous factors (Wang et al 2012;Wang et al 2014) and ankyrinG (Shirahata et al 2006;Gasser et al 2012) are identified as important interacting partners of Nav channels. They regulate Nav trafficking, expression pattern and gating in isoform-and cell type-specific manners (Deschênes et al 2002;Herzog et al 2003;Chichili et al 2013;Ben-Johny et al 2014;Barbosa et al 2017;Yan et al 2017).…”
Section: R850qmentioning
confidence: 99%
“…Over recent years, Nav β subunits have gained increasing scientific interest because they appear to be the only known proteins that participate in cell adhesion, are part of a channel complex, and function as intra/extracellular signalling molecules (Hull & Isom, ). In this study, we reveal a novel feature of β subunit‐mediated ion channel modification: the β1 subunit is able to influence the mechanical susceptibility of Nav1.7.…”
Section: Discussionmentioning
confidence: 99%